Global burden, trends, and inequalities of ischemic heart disease among young adults from 1990 to 2019: a population-based study - Wu, Peng; Yu, Shuixiu; Wang, Jun; Zou, Shenglan; Yao, De-Shan; Xiaochen, Yuan (Frontiers in Cardiovascular Medicine, 2023)
Background: Ischemic heart disease (IHD) is a major global health concern, and its burden among young adults aged 25-49 years remains underexplored. This study aims to provide a comprehensive assessment of the global burden and trends of IHD over the past 30 years among this age group, as well as to analyze the health inequalities related to socioeconomic development.Methods: Data from Global Burden of Disease Study 2019 (GBD 2019) were utilized to analyze the prevalence, mortality, and disability-adjusted life years (DALYs) rate of IHD among young adults globally. Joinpoint regression analysis was applied to examine the trends over the study period. Health inequality analysis was performed to investigate the disparities in IHD burden related to the Socio-Demographic Index (SDI) of countries.